RANCANG BANGUN SISTEM INFORMASI PENGARSIPAN SURAT MENYURAT (STUDI KASUS FAKULTAS TEKNIK UNP) - Geovanne Farell; Hadi Kurnia Saputra; Igor Novid (Jurnal Teknologi Informasi dan Pendidikan, 2018)
Technological developments are increasing rapidly along with the times. Filing is something that can not be separated from an organization or an institution, the archives have such an important role. the number of letters created and received administratively, so that the search data will be inefficient in terms of time and energy by using the manual system. So at this time required a system of administration of mail management more structured in order to accelerate the search for existing data and making reports, so the authors feel the need to design an application correspondence Archive is considered necessary and assist the department. This app is designed using PHP and MySQL. Because the web-based, this archive application has the ability, can be accessed anywhere, admin can manage with user login so that can do add, edit, delete and save incoming and outgoing mail, can do incoming mail and outbound mail based on sender and subject, print a report. The results obtained from the implementation of this correspondence archive application is to facilitate the department in managing the archiving of letters that used to manual now become digital, and very helpful lecturers in making the letter on the academic side of the electronics department of UNP.